2018
DOI: 10.33546/bnj.386
|View full text |Cite
|
Sign up to set email alerts
|

Effort to Reduce Anxiety Levels Among Mothers Using Febrile Convulsions Educational Package

Abstract: Background: Parents often experience anxiety when seeing their children having febrile convulsion. It may be due to lack of knowledge about febrile seizure and the way of handling it.Objective: This study aims to analyze the education package of febrile convulsion and its effect on mother’s anxiety.Methods: This was a quasi-experimental study with pretest posttest with control group design.  Eighty-one participants were selected, which randomly assigned to be two groups that 41 participants in control group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In addition, it was determined that the training package about FC had an important effect on the anxiety of the mothers of children with FC who were treated in the hospital. In a similar study by Rofiqoh et al [18] it was concluded that the FC training package could be used as an alternative treatment to reduce anxiety levels in mothers. In our study, we found that the anxiety level of these families was high in accordance with the literature.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it was determined that the training package about FC had an important effect on the anxiety of the mothers of children with FC who were treated in the hospital. In a similar study by Rofiqoh et al [18] it was concluded that the FC training package could be used as an alternative treatment to reduce anxiety levels in mothers. In our study, we found that the anxiety level of these families was high in accordance with the literature.…”
Section: Discussionmentioning
confidence: 96%
“…Satisfaction levels for caregivers whose child had experienced febrile seizures, who had difficulty getting up at night, and who experienced the benefits of continuous monitoring were particularly high. Parents whose children had experienced febrile seizures tended to be especially anxious when their children felt sick [ 6 , 21 , 22 ], and tended to use excessive amounts of antipyretics [ 23 ]. The continuous monitoring characteristics of the TempTraq ® may be helpful in relieving the anxiety of these parents who are particularly sensitive to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluasi dilakukan dengan State Anxiety Inventory in Indonesian version. Pemberian paket edukasi dapat menurunkan kecemasan anak dengan kejang demam (Rofiqoh & Isyti'aroh, 2018).…”
Section: Pembahasanunclassified